Hadith #2213 - Sunan Abi Dawud - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Ibn Ishaq محمد بن إسحاق بن يسار‎; Ma'mr bin 'Abdullah معمر بن عبد الله بن حنظلة; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان; Yusuf bin 'Abdullah bin Salam (Sunan Abi Dawud)
I was a man who was more given than others to sexual intercourse with women. When the month of Ramadan came, I feared lest I should have intercourse with my wife, and this evil should remain with me till the morning. So I made my wife like my mother’s back to me till the end of Ramadan. But one night when she was waiting upon me, something of her was revealed. Suddenly I jumped upon her. When the morning came I went to my people and informed them about this matter. I said: Go along with me to
Grade: Hasan

Hadith #2561 - Sunan Abi Dawud - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; ibn Abbas; Mujahid bin Jabir مجاهد بن جبر; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان (Sunan Abi Dawud)
‘Imran bin Hussain said “The Prophet (ﷺ) was on a journey. He heard a curse. He asked “What is this? They (the people) said “This is so and so (a woman) who cursed her riding beast. The Prophet (ﷺ) said “Remove the saddle from it, for it is accursed. So, they removed (the saddle) from it. ‘Imran said “As if I am looking at it a grey she Camel.”
Grade: Sahih

Hadith #2591 - Sunan Abi Dawud - Ammar bin Mua'wiya bin Aslam al-Dahni عمار بن معاوية الدهني; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Sharayk bin 'Abdullah شريك بن عبد الله النخعي; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان (Sunan Abi Dawud)
Yunus ibn Ubayd, client of Muhammad ibn al-Qasim, said that Muhammad ibn al-Qasim sent to al-Bara’ ibn Azib to ask him about the standard of the Messenger of Allah (ﷺ). He said: It was black and square, being made of a woollen rug.
Grade: Sahih

Hadith #2613 - Sunan Abi Dawud - Anas ibn Malik; Ubaidullah bin Musa bin Abi al-Mukhtar عبيد الله بن موسى بن أبي المختار باذام; Uthman bin Muhammad; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان (Sunan Abi Dawud)
Sulaiman bin Buraidah reported on his father’s authority The Prophet(ﷺ) said “Fight in the name of Allaah and in the path of Allaah and with him who disbelieves in Allaah fight and do not be treacherous and do not be dishonest about boot yand do not deface (in killing) and do not kill a child.”
Grade: Sahih

Hadith #2903 - Sunan Abi Dawud - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Burayda bin al-Husayb; Sharayk bin 'Abdullah شريك بن عبد الله النخعي; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان (Sunan Abi Dawud)
A man came to the Messenger of Allah (ﷺ) and said: I have property left by a man of Azd. I do not find any man of Azd to give it to him. He said: Go and look for man of Azd for a year. He then came to him after one year and said: Messenger of Allah, I did not find any man of Azd to give it to him. He said: Look for a man of Khuza’ah whom you meet first and give it to him. When he turned away, he said; Call the man to me. When he came to him, he said: Look for the leading man of Khuza’ah an
Grade: Da'if

Hadith #3010 - Sunan Abi Dawud - al-Husain bin 'Ali bin al-Walid al-Ja'fi الحسين بن علي بن الوليد الجعفي; Bashayr bin al-Yasar al-Harithi al-Ansar بشير بن يسار مولى بني حارثة; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان; Yahya bin Sa'id al-Ansari يحيى بن سعيد الأنصاري (Sunan Abi Dawud)
Sahl bin Abi Hathmah said “The Apostle of Allaah(ﷺ) divide Khaibar into two halves. One half was reserved for his emergency and needs, the other half was meant for the Muslims. He divided among them into eighteen portions.”
Grade: Hasan Sahih

Hadith #3015 - Sunan Abi Dawud - Abdullah bin Abi Bakr bin Muh. b. 'Amr عبد الله بن أبي بكر بن محمد بن عمرو; al-Husain bin 'Ali bin al-Walid al-Ja'fi الحسين بن علي بن الوليد الجعفي; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ibn Ishaq محمد بن إسحاق بن يسار‎; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان; Yahya bin Zakaria bin Abi Zaida يحيى بن زكريا بن أبي زائدة (Sunan Abi Dawud)
Khaybar was divided among the people of al-Hudaybiyyah. The Messenger of Allah (ﷺ) divided it into eighteen portions. The army contained one thousand and five hundred people. There were three hundred horsemen among them. He gave double share to the horsemen, and a single to the footmen.
Grade: Hasan

Hadith #3020 - Sunan Abi Dawud - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; ibn Abbas; Ibn Ishaq محمد بن إسحاق بن يسار‎; Ubaydullah bin 'Abdullah bin 'Utba عبيد الله بن عبد الله بن عتبة بن مسعود; Uthman bin Muhammad; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان (Sunan Abi Dawud)
‘Umar said “Had I not considered the last Muslim, I would have any town I conquered divided as the Apostle of Allaah(ﷺ) had divided Khaibar.”
Grade: Sahih

Hadith #3068 - Sunan Abi Dawud - Abu Bakr bin 'Ayyash al-Asadi أبو بكر بن عياش بن سالم الأسدي; al-Husain bin 'Ali bin al-Walid al-Ja'fi الحسين بن علي بن الوليد الجعفي; Asma' bint Abi Bakr; Hisham bin 'Urwa هشام بن عروة; Urwa ibn al-Zubayr عروة بن الزبير; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان (Sunan Abi Dawud)
The Prophet (ﷺ) alighted at a place where a mosque has been built under a large tree. He tarried there for three days, and then proceeded to Tabuk. Juhaynah met him on a wide plain. He asked them: who are the people of Dhul-Marwah? They replied: Banu Rifa’ah of Juhaynah. He said: I have given this (land) to Banu Rifa’ah as a fief. Therefore, they divided it. Some of them sold (their share) and others retained and worked on it. (Sub-narrator Ibn Wahab said: I then asked AbdulAziz about this
Grade: Hasan

Hadith #3223 - Sunan Abi Dawud - Abdullah bin Mubarak عبد الله بن المبارك; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Haywat bin Sharih bin Safwan حيوة بن شريح بن صفوان التجيبي; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان; Yazid bin Abi Habib يزيد بن أبي حبيب (Sunan Abi Dawud)
One day the Messenger of Allah (ﷺ) went out and prayed over the martyrs of Uhud like his prayer over the dead, and then returned.
Grade: Sahih

Hadith #3544 - Sunan Abi Dawud - Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Muhammad bin Rafa'i محمد بن رافع; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
The Prophet (ﷺ) said: Act equally between your children; Act equally between your sons.
Grade: Sahih

Hadith #3605 - Sunan Abi Dawud - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; ibn Abbas; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان; Yahya bin Zakaria bin Abi Zaida يحيى بن زكريا بن أبي زائدة; Zakaria bin Abi Za'idah زكريا بن أبي زائدة خالد (Sunan Abi Dawud)
A Muslim was about to die at Daquqa’, but he did not find any Muslim to call him for witness to his will. So he called two men of the people of the Book for witness. Then they came to Kufah, and approaching AbuMusa al-Ash’ari they informed him (about his) will. They brought his inheritance and will. Al-Ash’ari said: This is an incident (like) which happened in the time of the Messenger of Allah (ﷺ) and never occurred after him. So he made them to swear by Allah after the afternoon prayer
Grade: Da'if

Hadith #3613 - Sunan Abi Dawud - Abdul Rahim bin Sulaiman عبد الرحيم بن سليمان الكناني; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان (Sunan Abi Dawud)
Two men claimed a camel or an animal and brought the case to the Holy Prophet (ﷺ). But as neither of them produced any proof, the Holy Prophet (ﷺ) declared that they should share it equally.
Grade: Hasan

Hadith #3675 - Sunan Abi Dawud - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; al-Nu'man bin Bashir ibn Sa'd; Amir al-Sha'bi عامر الشعبي; Ibrahim bin Mhajr bin Jabir إبراهيم بن مهاجر بن جابر; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان (Sunan Abi Dawud)
Abu Talhah asked the prophet (ﷺ) about the orphans who had inherited wine. He replied: Pour it out. He asked: May I not make vinegar of it ? He replied : No.
Grade: Sahih

Hadith #3700 - Sunan Abi Dawud - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان (Sunan Abi Dawud)
The Prophet(ﷺ) mentioned the vessels: pumpkins, green jarrs, vessels smeared with pitch and hollow stumps. A desert Arab said: We have no vessels(except these). He said: Drink(from them) what is lawful.
Grade: Sahih

Hadith #4866 - Sunan Abi Dawud - Abdur Rahman bin Ata'a عبد الرحمن بن عطاء; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Jabir ibn 'Abdullah; Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان (Sunan Abi Dawud)
‘Abbad b. Tamim quoted his paternal uncle as saying that he had seen the Messenger of Allah(ﷺ) lying on his back in the mosque according to Qa’nabi’s version) placing one foot over the other.
Grade: Sahih